2022
DOI: 10.2147/dmso.s385774
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-5p Promotes Glucose Uptake of HTR8/SVneo Trophoblast Cells by Inhibiting TXNIP/NLRP3 Inflammasome Pathway

Abstract: Gestational diabetes mellitus (GDM) is one of the common metabolic disorders of pregnancy and results in poor pregnancy outcomes for both mother and fetus. MiR-17-5p is considered as the strongest predictor of metabolic syndrome status, but the relationship between GDM and miR-17-5p remains unclear. TXNIP, which leads to activation of NLRP3, is considered as a potential target of miR-17-5p, and the miR-17-5p/TXNIP/NLRP3 axis has been shown to play a major role in the occurrence and development of many metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Cyanidin-3-O-glucoside protects endothelial cells by regulating the miR-204-5p/SIRT1-mediated inflammatory response and apoptosis ( Wang Z. et al, 2020 ). MiR-17-5p inhibits the TXNIP/NLRP3 inflammatory pathway and promotes glucose uptake in HTR8/SVneo trophoblast cells ( Jiang et al, 2022 ). Downregulation of miR-17-5p alleviates apoptosis and fibrosis in human renal interstitial cells induced by high glucose ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cyanidin-3-O-glucoside protects endothelial cells by regulating the miR-204-5p/SIRT1-mediated inflammatory response and apoptosis ( Wang Z. et al, 2020 ). MiR-17-5p inhibits the TXNIP/NLRP3 inflammatory pathway and promotes glucose uptake in HTR8/SVneo trophoblast cells ( Jiang et al, 2022 ). Downregulation of miR-17-5p alleviates apoptosis and fibrosis in human renal interstitial cells induced by high glucose ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yi et al confirmed that TXNIP was increased in placental samples of GDM patients, which was consistent with ours. It is reported that MiR-17-5p could up regulate the expression of TXNIP, improved glucose uptake of HTR-8/Svneo cells by TXNIP/NLRP3 axis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Additionally, recent studies reported that inhibiting the TXNIP/NLRP3 inflammasome pathway increased glucose absorption in HTR8/ SVneo trophoblast cells, suggesting that miR-17-5p may be a potential target for reducing insulin resistance and treating DM. 78 The study found that the expression level of KCNQ10OT1 in the serum of diabetic patients was higher than that of healthy individuals in the control group. 85 Thus, the lncRNA-miRNA-mRNA interaction network can be a target for regulating the onset and progression of diabetes.…”
Section: The Mechanism Of Ncrna-regulate Pyroptosis In Diabetesmentioning
confidence: 90%
“…In HG‐treated INS‐1 pancreatic β cells of rats and an HFD/STZ mice model, miR‐17‐5p mimics rescued insulin secretion dysfunction by suppressing the activation of the TXNIP/NLRP3 inflammasome pathway 17 . Additionally, recent studies reported that inhibiting the TXNIP/NLRP3 inflammasome pathway increased glucose absorption in HTR8/SVneo trophoblast cells, suggesting that miR‐17‐5p may be a potential target for reducing insulin resistance and treating DM 78 . The study found that the expression level of KCNQ10OT1 in the serum of diabetic patients was higher than that of healthy individuals in the control group 85 .…”
Section: The Mechanism Of Ncrna‐regulated Pyroptosis In Diabetes and Vcdmentioning
confidence: 99%